Choice and impact of frequency increment in direct digital synthesiser (DDS)‐based linear FMCW radar - Paul Victor Brennan; Lai Bun Lok (IET Radar, Sonar & Navigation, 2023)
Abstract FMCW radar is a popular technique for radar sensors. A Direct Digital Synthesiser (DDS) is commonly used to generate the required linear frequency sweep. DDS devices are widely‐available and easy to configure in terms of the key radar parameters of sweep bandwidth and pulse duration. They generate a step‐approximation to a linear frequency sweep for which the frequency increment parameter also needs to be defined. However, there is little information available in the literature to guide radar designers on the choice of this parameter. As a result, most designs are based on an empirical estimate of the DDS frequency increment. The aim is to provide an analytic basis and design rules for the choice of this parameter. Two principal types of FMCW radar (direct sampling and deramp) are studied to determine the effect on the range profile of the finite DDS frequency increment. It is shown that a set of spurs appears around each target response. Analytic expressions are derived to quantify the amplitude and distribution of these spurs from which simple design rules are presented to allow an informed choice of DDS frequency increment. These analytic results are convincingly validated using numerical simulations and experimental measurements.